Core-stable rings in second price auctions with common values - Françoise Forges; Ram Orzach (Fondazione Eni Enrico Mattei (FEEM), 2010)
In a common value auction in which the information partitions of the bidders are connected, all rings are core-stable. More precisely, the ex ante expected utilities of rings, at the (noncooperative) sophisticated equilibrium proposed by Einy, Haimanko, Orzach and Sela (Journal of Mathematical Economics, 2002), describe a cooperative game, in characteristic function form, in spite of the underlying strategic externalities. A ring is core-stable if the core of this characteristic function is not empty. Furthermore, every ring can implement its sophisticated equilibrium strategy by means of an incentive compatible mechanism.
Keywords: C71; C72; D44; 330; Auctions; Bayesian game; Collusion; Core; Partition form game; Characteristic function